2011
DOI: 10.25130/tjes.18.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static Soaking under Different Temperatures on the Lime Stabilized Gypseous Soil

Abstract: This study concerns with the effect of long-term soaking on the unconfined compressive strength, loss in weight and gypsum dissolution of gypseous soil stabilized with (4%) lime, take into account the following variables: initial water content, water temperature, soaking duration.The results reveals that, the unconfined compressive strength was dropped, and the reduction in values was different according to the initial water content and water temperature, so that the reduction of the unconfined compressive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Several researchers attempted to examine the effect of various additions on the behavior of gypseous soils. Al-Zory [8] demonstrated that adding 5-7% lime with gypseous soil containing 43% gypsum increased the soil's strength and resistance to leaching. It has been stated that after 28 days of curing, the soil became essentially impermeable.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers attempted to examine the effect of various additions on the behavior of gypseous soils. Al-Zory [8] demonstrated that adding 5-7% lime with gypseous soil containing 43% gypsum increased the soil's strength and resistance to leaching. It has been stated that after 28 days of curing, the soil became essentially impermeable.…”
Section: Introductionmentioning
confidence: 99%